L’émergence par la créativité au Cap - Thomas Radovcic (EchoGéo)
From 2005, the stakeholders involved in the Capetonian urban governance adopted an urban development programme to promote the creative economy and “creative industries” in the central city. Nonetheless, whereas social, spatial and racial inequalities inherited from the apartheid era are still persisting, this strategy aims to strengthen Cape Town’s assets to internationally compete with other cities. It does not foster the “emergence” of previously disadvantaged groups and places from poverty and underdevelopment.